Solvent-free flame-retardant insulating battery cell uv inkjet coating and preparation method

CN122898211APending Publication Date: 2026-10-13HAINAN WEIXIN MATERIAL TECHNOLOGY (SHENZHEN) CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611210952.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0007]本发明的主要目的是为了提供一种无溶剂阻燃绝缘电芯用UV喷墨涂料及制备方法,通过分子骨架为有机聚硅氮烷与1,9-壬二醇二丙烯酸酯(NDDA)经硅氢加成接枝改性制备低聚物,搭配金刚烷类钻石笼状丙烯酸酯UV单体,解决现有技术中电芯UV喷墨绝缘涂料工艺对于低粘度喷墨要求与高性能指标无法同时满足的技术问题

Benefits of technology

[0021]S4、避光助剂复配:浆料降温至40℃以下,避光环境下加入UV复配光引发剂、UV功能助剂,低速避光搅拌10-20min混合均匀;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses a kind of solventless flame-retardant insulating electric core UV inkjet coating, by mass fraction count, including by mass fraction count, including: polysilazane grafting NDDA oligomer: 40-50 parts;Diamond cage-shaped acrylate monomer: 30-40 parts;Polyurethane polycarbonate acrylate resin: 10-20 parts;UV compound photoinitiator: 6-8 parts;Nano insulating flame-retardant functional filler: 1-2 parts;UV special functional additive: 0.5-2.0 parts.This coating is solventless full curing system, relies on diamond cage-shaped structure + silazane to realize low viscosity and high performance, system viscosity adapts UV inkjet process, coating after curing has high insulation, high flame-retardant, electrolyte resistance and moisture heat aging performance, can satisfy the rigorous demand of power electric core insulation protection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coatings, and more particularly to a solvent-free flame-retardant insulating UV inkjet coating for battery cells and its preparation method. Background Technology

[0002] With the rapid popularization of high-voltage fast charging technology for new energy vehicles, the performance requirements for cell insulation and protection materials in power battery systems have significantly increased. Cell insulation and protection materials are functional protective layers covering the surface of the power battery cell casing. Their core function is to construct a stable electrical insulation barrier between the cell and the module casing, and between adjacent cells, preventing short-circuit faults. They also possess functions such as resistance to electrolyte corrosion, resistance to damp heat aging, flame retardancy and heat insulation, and mechanical buffering. They are core protective materials ensuring the electrical safety and long-term service reliability of power battery systems. Current cell insulation and protection technology has mainly undergone three generations of development:

[0003] The first generation uses a composite process of spraying insulating powder and attaching a PET blue film. This process achieves insulation protection by first spraying insulating powder and then attaching a PET blue film. However, the breakdown voltage of the PET blue film can only reach 800V, which cannot meet the high-voltage safety requirements of fast charging scenarios. At the same time, the blue film relies on pressure-sensitive adhesive for bonding, which is prone to problems such as edge lifting, wrinkling, and falling off. It also has poor resistance to electrolyte and damp heat aging, and the multi-layer composite structure is difficult to recycle, resulting in insufficient environmental friendliness.

[0004] The second generation is the UV spraying insulating coating process. This solution replaces the PET blue film with UV-cured coating, which significantly improves insulation withstand voltage and protection reliability and has high production efficiency. However, the UV spraying process has a material waste problem of 15%-20%, and there is still room for optimization of the overall cost.

[0005] The third generation is UV inkjet insulating coating technology, which is also the industry's research and development direction. UV inkjet technology uses a printhead spraying method similar to a printer, with almost no material waste, and can adapt to the needs of different market levels, from high-end to low-end. However, this technology places stringent requirements on the performance of the coating. First, the viscosity of the UV inkjet insulating coating must be below 100 cps, otherwise it will easily clog the printhead; the fineness requirement is extremely high to avoid particles clogging the inkjet channels; and because the amount of resin added in the formula is very small, the core performance is almost entirely achieved by monomers that can participate in the curing reaction.

[0006] In the existing technology, based on the above-mentioned stringent requirements, the existing conventional monomer products on the market cannot simultaneously meet the technical requirements of low viscosity inkjet printing and high performance indicators (high insulation, high flame retardancy, electrolyte resistance, etc.). Summary of the Invention

[0007] The main objective of this invention is to provide a solvent-free, flame-retardant, insulating UV inkjet coating for battery cells and its preparation method. This invention utilizes an oligomer prepared by hydrosilylation grafting of an organopolysilazane and 1,9-nonanediol diacrylate (NDDA) with a molecular skeleton, combined with adamantane-based diamond cage-like acrylate UV monomer. This addresses the technical problem in existing battery cell UV inkjet insulating coating processes where low-viscosity inkjet printing requirements and high-performance indicators cannot be simultaneously met.

[0008] The first aspect of this invention provides a solvent-free flame-retardant insulating UV inkjet coating for battery cells, comprising, by weight: 40-50 parts of polysilazane-grafted NDDA oligomer; 30-40 parts of adamantane-based diamond cage-like acrylate monomer; 10-20 parts of polyurethane polycarbonate acrylate resin; 6-8 parts of UV-complexed photoinitiator; 1-2 parts of nano-insulating and flame-retardant functional filler; and 0.5-2.0 parts of UV-specific functional additives.

[0009] Optionally, the polysilazane-grafted NDDA oligomer is prepared by grafting an organosilazane with 1,9-nonanediol diacrylate (NDDA) via a hydrosilylation reaction.

[0010] Optionally, the adamantane-based diamond cage-like acrylate monomer is a blend of at least two of 1,3-adamantane diol diacrylate, 1-adamantane methyl methacrylate, and adamantane monovinyl ether.

[0011] Optionally, the UV composite photoinitiator is composed of 2,4,6-trimethylbenzoyl diphenylphosphine oxide (TPO) and 1-hydroxycyclohexylphenyl ketone (184).

[0012] Optionally, the polyurethane polycarbonate acrylate resin is a bifunctional flexible polyurethane acrylate synthesized by stepwise addition of aliphatic polycarbonate diol, diisocyanate, and hydroxyethyl acrylate.

[0013] Optionally, the nano-insulating and flame-retardant functional filler is a composite system of nano-fumed silica, nano-aluminum nitride, and modified phosphorus-based nano-flame-retardant powder.

[0014] Optionally, the UV-specific functional additive includes a polyether-modified silicone leveling agent, an acrylate defoamer, and a hindered phenolic UV storage inhibitory stabilizer.

[0015] Optionally, the preparation process of the polysilazane-grafted NDDA oligomer is as follows: under nitrogen inert atmosphere protection, the organopolysilazane is heated to 70-80°C, NDDA monomer and platinum-based hydrosilylation catalyst are added dropwise, the reaction is maintained at the temperature for 5-7 hours, after the reaction is completed, trace amounts of small molecule by-products are removed under vacuum, and the transparent oligomer is obtained by cooling and discharging.

[0016] In summary, this invention discloses a solvent-free, flame-retardant, insulating UV inkjet coating for battery cells, comprising, by weight: 40-50 parts of polysilazane-grafted NDDA oligomer; 30-40 parts of adamantane-based diamond cage-like acrylate monomer; 10-20 parts of polyurethane polycarbonate acrylate resin; 6-8 parts of UV-coated photoinitiator; 1-2 parts of nano-insulating and flame-retardant functional filler; and 0.5-2.0 parts of UV-specific functional additives. This coating uses polysilazane-silyl hydrografted 1,9-nonanediol diacrylate (NDDA) as the main film-forming matrix, compounded with adamantane-based diamond cage-like acrylate monomer, polyurethane polycarbonate acrylate resin, LED-coated photoinitiator, nano-insulating and flame-retardant filler, and UV-specific functional additives, forming a 100% solid-content, solvent-free system. The three-dimensional saturated cage-like carbon skeleton of adamantane significantly reduces molecular chain entanglement, achieving a low viscosity system with viscosity controlled at 10-100 cps at 25℃. This perfectly adapts to continuous printing with piezoelectric UV inkjet equipment, eliminating printhead clogging and crystallization issues. By grafting long-chain diacrylates of NDDA onto polysilazane, active acrylic double bonds and compatible segments are introduced into the inorganic silicon-nitrogen backbone, solving industry pain points such as poor compatibility between pure polysilazane and acrylic monomers and polyurethane resins, and coating delamination failure during storage. After curing, the coating forms a dual protective structure of a silazane ceramic barrier layer and adamantane dense cage-like network, possessing ultra-high electrical insulation, high-temperature ceramic flame retardancy, long-lasting resistance to lithium battery electrolyte immersion, resistance to 85℃ / 85RH damp heat aging, and resistance to thermal cycling cracking. This meets the stringent safety requirements for precision localized insulation coating of new energy power battery cells and aluminum shells, with zero VOC emissions throughout the process, high coating utilization, and strong industrial adaptability.

[0017] The second aspect of this invention provides a method for preparing a solvent-free flame-retardant insulating UV inkjet coating for battery cells, used to prepare the solvent-free flame-retardant insulating UV inkjet coating for battery cells as described in any optional embodiment of the first aspect, comprising the following steps:

[0018] S1. Resin premixing: Add polysilazane-grafted NDDA oligomer and polyurethane polycarbonate acrylate resin to a room temperature sealed dispersion vessel, and stir at low speed for 5-10 minutes until the system is completely miscible and transparent;

[0019] S2. Low viscosity control: Add adamantane-based diamond cage-like acrylate monomers in batches, stir at medium speed for 10-20 minutes, monitor the viscosity online, and control the viscosity of the finished product system at 25℃ to 10-100 cps.

[0020] S3. Filler dispersion and grinding: Add nano-insulating and flame-retardant composite filler, disperse at high speed for 10-20 minutes, then transfer to a sand mill for circulating grinding until the slurry particle size D50 < 0.5 μm;

[0021] S4. Light-shielding additive compounding: Cool the slurry to below 40℃, add UV compound photoinitiator and UV functional additive in a light-shielding environment, and mix evenly by low-speed light-shielding stirring for 10-20 minutes.

[0022] S5. Precision filtration and packaging: Impurities are filtered using two-stage 0.2μm PTFE precision filter membranes, and the product is stored in a light-proof and sealed environment to obtain a solvent-free UV inkjet insulating coating.

[0023] In summary, this invention discloses a method for preparing a solvent-free flame-retardant insulating UV inkjet coating for power battery cells. The steps include: dissolving polysilazane-grafted NDDA oligomer and polyurethane polycarbonate acrylate resin by stirring to obtain a pre-dispersion; adding adamantane-based diamond cage-like acrylate monomer and stirring until homogeneous; adding nano-insulating and flame-retardant composite filler and dispersing at high speed; adding a compounded photoinitiator and UV functional additives after cooling and stirring at low speed in the dark until homogeneous; and finally, bottling after precision filtration. This process is simple and controllable, requires no special equipment, and can be produced using existing UV coating production lines. The resulting coating has stable viscosity and meets the required fineness, and can be directly adapted to mainstream UV inkjet equipment, meeting the mass production needs of insulating coating for power battery cells. Detailed Implementation

[0024] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0025] It should be understood that, when used in this specification and the appended claims, the terms "comprising" and "including" indicate the presence of the described features, integrals, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, integrals, steps, operations, elements, components and / or collections thereof.

[0026] It should also be understood that the terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. As used in this specification and the appended claims, the singular forms “a,” “an,” and “the” are intended to include the plural forms unless the context clearly indicates otherwise.

[0027] It should also be further understood that the term "and / or" as used in this specification and the appended claims refers to any combination of one or more of the associated listed items and all possible combinations, and includes such combinations.

[0028] With the rapid popularization of high-voltage fast charging technology for new energy vehicles, the performance requirements for cell insulation and protection materials in power battery systems have significantly increased. Cell insulation and protection materials are functional protective layers covering the surface of the power battery cell casing. Their core function is to construct a stable electrical insulation barrier between the cell and the module casing, and between adjacent cells, preventing short-circuit faults. They also possess functions such as resistance to electrolyte corrosion, resistance to damp heat aging, flame retardancy and heat insulation, and mechanical buffering. They are core protective materials ensuring the electrical safety and long-term service reliability of power battery systems. Current cell insulation and protection technology has mainly undergone three generations of development:

[0029] The first generation uses a composite process of spraying insulating powder and attaching a PET blue film. This process achieves insulation protection by first spraying insulating powder and then attaching a PET blue film. However, the breakdown voltage of the PET blue film can only reach 800V, which cannot meet the high-voltage safety requirements of fast charging scenarios. At the same time, the blue film relies on pressure-sensitive adhesive for bonding, which is prone to problems such as edge lifting, wrinkling, and falling off. It also has poor resistance to electrolyte and damp heat aging, and the multi-layer composite structure is difficult to recycle, resulting in insufficient environmental friendliness.

[0030] The second generation is the UV spraying insulating coating process. This solution replaces the PET blue film with UV-cured coating, which significantly improves insulation withstand voltage and protection reliability and has high production efficiency. However, the UV spraying process has a material waste problem of 15%-20%, and there is still room for optimization of the overall cost.

[0031] The third generation is UV inkjet insulating coating technology, which is also the industry's research and development direction. UV inkjet technology uses a printhead spraying method similar to a printer, with almost no material waste, and can adapt to the needs of different market levels, from high-end to low-end. However, this technology places stringent requirements on the performance of the coating. First, the viscosity of the UV inkjet insulating coating must be below 100 cps, otherwise it will easily clog the printhead; the fineness requirement is extremely high to avoid particles clogging the inkjet channels; and because the amount of resin added in the formula is very small, the core performance is almost entirely achieved by monomers that can participate in the curing reaction.

[0032] In the existing technology, based on the above-mentioned stringent requirements, the existing conventional monomer products on the market cannot simultaneously meet the technical requirements of low viscosity inkjet printing and high performance indicators (high insulation, high flame retardancy, electrolyte resistance, etc.).

[0033] To address the aforementioned issues, this application provides a solvent-free, flame-retardant, insulating UV inkjet coating for battery cells. This coating utilizes an oligomer prepared by hydrosilylation grafting of an organopolysilazane and 1,9-nonanediol diacrylate (NDDA) with a molecular skeleton. This oligomer is then combined with adamantane-based diamond cage-like acrylate UV monomer, satisfying the stringent requirements of the battery cell UV inkjet insulating coating process for low-viscosity inkjet printing and high-performance indicators.

[0034] For ease of understanding, a detailed explanation is provided below.

[0035] Example 1

[0036] A solvent-free, flame-retardant, insulating UV inkjet coating for battery cells, comprising, by weight:

[0037] Polysilazane-grafted NDDA oligomer: 40 parts

[0038] 1,3-Adamantanediol diacrylate: 17.5 parts

[0039] 1-Adamantyl methacrylate: 18 parts

[0040] Polyurethane polycarbonate acrylate resin: 15 parts

[0041] TPO photoinitiator: 4 parts

[0042] 184 photoinitiator: 3 parts

[0043] Nano-sized fumed silica: 0.5 parts

[0044] Nano-aluminum nitride: 0.4 parts

[0045] Modified phosphorus-based nano flame retardant powder: 0.3 parts

[0046] Polyether-modified silicone leveling agent: 0.5 parts

[0047] Acrylic defoamer: 0.3 parts

[0048] Hindered phenolic UV storage polymerization stabilizer: 0.5 parts

[0049] Example 2

[0050] A solvent-free, flame-retardant, insulating UV inkjet coating for battery cells, comprising, by weight:

[0051] Polysilazane-grafted NDDA oligomer: 40 parts

[0052] 1,3-Adamantanediol diacrylate: 17.5 parts

[0053] adamantane monovinyl ether: 18 parts

[0054] Polyurethane polycarbonate acrylate resin: 15 parts

[0055] TPO photoinitiator: 4 parts

[0056] 184 photoinitiator: 3 parts

[0057] Nano-sized fumed silica: 0.5 parts

[0058] Nano-aluminum nitride: 0.4 parts

[0059] Modified phosphorus-based nano flame retardant powder: 0.3 parts

[0060] Polyether-modified silicone leveling agent: 0.5 parts

[0061] Acrylic defoamer: 0.3 parts

[0062] Hindered phenolic UV storage polymerization stabilizer: 0.5 parts

[0063] Example 3

[0064] A solvent-free, flame-retardant, insulating UV inkjet coating for battery cells, comprising, by weight:

[0065] Polysilazane-grafted NDDA oligomer: 40 parts;

[0066] 1-Adamantyl methacrylate: 17.5 parts

[0067] adamantane monovinyl ether: 18 parts

[0068] Polyurethane polycarbonate acrylate resin: 15 parts

[0069] TPO photoinitiator: 4 parts

[0070] 184 photoinitiator: 3 parts

[0071] Nano-sized fumed silica: 0.5 parts

[0072] Nano-aluminum nitride: 0.4 parts

[0073] Modified phosphorus-based nano flame retardant powder: 0.3 parts

[0074] Polyether-modified silicone leveling agent: 0.5 parts

[0075] Acrylic defoamer: 0.3 parts

[0076] Hindered phenolic UV storage polymerization stabilizer: 0.5 parts

[0077] The test results after inkjet printing and curing of the above embodiments using a piezoelectric UV inkjet printer are as follows:

[0078] Viscosity 45cps 37cps 42cps Fineness <0.5μm <0.5μm <0.5μm Solid content 100% 100% 100% Film thickness 100μm 100μm 100μm Adhesion Level 0 Level 0 Level 0 hardness 2H 2H 2H Pressure resistance >3500V >3500V >3500V Breakdown voltage ≥18kV / mm ≥18kV / mm ≥18kV / mm Flame retardant UL94-V0 UL94-V0 UL94-V0 Electrolyte resistant 720H 720H 720H Hot and cold circulation 500 times 500 times 500 times 85℃ / 85RH damp heat aging 1000H 1000H 1000H

[0079] In the above embodiments, the functions and technical principles of each component are as follows:

[0080] Polysilazane-grafted NDDA oligomer: This is the core functional component of the formulation. It involves covalently grafting long-chain NDDA diacrylate onto polysilazane via hydrosilylation. This retains the inorganic advantages of polysilazane, such as high dielectric insulation, high-temperature ceramic flame retardancy, and dense barrier properties. Furthermore, the long alkyl chain of NDDA addresses three major industry bottlenecks: introducing UV-active double bonds to achieve room-temperature LED curing; building an organic-inorganic compatibility bridge to prevent coating delamination; weakening molecular entanglement to reduce system viscosity and adapt to UV inkjet processes; and simultaneously, flexible carbon chains to improve coating brittleness and cracking, perfectly matching the stringent requirements of precision inkjet insulation protection for power battery boxes. Optionally, the polysilazane-grafted NDDA oligomer is prepared by hydrosilylation grafting modification of organopolysilazane with 1,9-nonanediol diacrylate (NDDA).

[0081] Adamantane-based diamond cage-like acrylate monomers: The extremely low molecular entanglement of the three-dimensional cage-like saturated carbon structure of adamantane significantly reduces the viscosity of the system without the addition of volatile solvents and low-performance common diluent monomers. The viscosity of the coating at 25°C is controlled at 10-100 cps, which is perfectly compatible with piezoelectric UV inkjet equipment for long-term continuous printing without printhead clogging or crystal precipitation problems. Optionally, the adamantane-based diamond cage-like acrylate monomers include at least two of the following: 1,3-adamantane diol diacrylate, 1-adamantyl methacrylate, and adamantane monovinyl ether.

[0082] UV composite photoinitiator: This is a UV free radical polymerization initiator that cleaves under UV light to generate active free radicals, initiating a chain polymerization reaction between the monomer and the acrylate double bonds in the resin, driving the coating to rapidly crosslink and form a film. Optionally, the UV composite photoinitiator comprises a combination of 2,4,6-trimethylbenzoyl diphenylphosphine oxide (TPO) and 1-hydroxycyclohexylphenyl ketone (184).

[0083] Polyurethane polycarbonate acrylate resin: A bifunctional polyurethane polycarbonate acrylate synthesized from aliphatic polycarbonate diol, diisocyanate, and hydroxyethyl acrylate. The molecular chain is rich in flexible carbonate segments, neutralizing the high rigidity defects caused by polysilazane and adamantane monomers, significantly improving coating toughness and adhesion to aluminum battery box substrates, enhancing crack resistance under thermal cycling conditions, and improving coating adhesion after damp heat aging. Optionally, the polyurethane polycarbonate acrylate resin is a bifunctional flexible polyurethane acrylate synthesized by stepwise addition of aliphatic polycarbonate diol, diisocyanate, and hydroxyethyl acrylate.

[0084] Nano-insulating and flame-retardant functional filler: Nano-fumed silica improves coating density and dielectric strength; nano-aluminum nitride enhances insulation and thermal conductivity, balancing localized high temperatures in the battery cell; modified phosphorus-based nanoparticles synergistically achieve flame retardancy in expanded ceramics. Optionally, the nano-insulating and flame-retardant functional filler includes a composite system of nano-fumed silica, nano-aluminum nitride, and modified phosphorus-based nano-flame-retardant powder.

[0085] UV-specific functional additives include: polyether-modified silicone leveling agents to eliminate inkjet pinholes and improve print uniformity; acrylate defoamers to eliminate microbubbles introduced by high-speed inkjet printing; and hindered phenolic polymerization inhibitors to extend the stability of coatings during light-protected storage. Optionally, UV-specific functional additives include polyether-modified silicone leveling agents, acrylate defoamers, and hindered phenolic UV storage polymerization inhibitors and stabilizers.

[0086] This embodiment can achieve the following core technical effects:

[0087] 1. Low viscosity, suitable for UV inkjet printing, solvent-free and environmentally friendly.

[0088] The adamantane cage structure weakens molecular entanglement, resulting in a stable system viscosity of 10–100 cps and 100% solids content with no VOCs. The industrial piezoelectric printhead can print continuously for 24 hours without clogging or crystal precipitation. It supports precise local graphic coating with a material utilization rate of >95%, far exceeding that of traditional air spraying.

[0089] 2. Excellent resin compatibility and strong storage stability.

[0090] NDDA long-chain diacrylate grafted modified polysilazane solves the problem of delamination and gloss loss between pure silazane and acrylic resin. The finished coating shows no precipitation, no gelation, and viscosity fluctuation of <5% after 6 months of storage in the dark.

[0091] 3. High insulation + ceramic flame retardant, suitable for thermal runaway protection of battery cells.

[0092] The coating has a breakdown voltage of ≥18kV / mm and a limiting oxygen index (LOI) of >32. At high temperatures, the polysilazane-converted ceramic insulation layer, with its dense adamantane network, suppresses molten dripping and blocks flame conduction, meeting the UL94V-0 flame retardant safety standard for power batteries.

[0093] 4. Excellent resistance to electrolyte and damp heat aging

[0094] The cage-like adamantane + silazane dual dense barrier structure blocks the channels for carbonate electrolyte and water vapor permeation; after immersion in 1MLiPF6 lithium battery electrolyte for 720h, the coating shows no swelling or peeling, and the insulation performance retention rate is ≥98%; after 1000h of 85℃ / 85RH dual 85 damp heat aging, there is no bubbling and the cross-cut adhesion is grade 0.

[0095] 5. Balanced rigidity and toughness, resistant to cracking under thermal cycling.

[0096] The flexible segments of polyurethane polycarbonate offset the brittle defects of rigid components; the battery cell can withstand 500 cycles of thermal cycling from -40℃ to 120℃ without cracking or peeling of the coating, making it suitable for the thermal expansion and contraction deformation of metal casings.

[0097] It should be noted that any specific combination of values ​​within the above-mentioned component weight range can achieve the technical effect of this application and is within the scope of protection of this application.

[0098] In summary, this invention discloses a solvent-free UV inkjet battery box insulating and flame-retardant coating and its preparation method, belonging to the field of new energy power battery photocurable coating technology. This coating uses polysilazane silane-grafted 1,9-nonanediol diacrylate (NDDA) as the main film-forming matrix, compounded with adamantane-based diamond cage-like acrylate monomers, polyurethane polycarbonate acrylate resin, and LED-compounded photoinitiators, nano-insulating and flame-retardant fillers, and UV-specific functional additives, resulting in a 100% solids-content solvent-free system. The three-dimensional saturated cage-like carbon skeleton of adamantane significantly reduces molecular chain entanglement, achieving a low viscosity system with a viscosity controlled at 10-100 cps at 25℃, perfectly adapting to continuous printing with piezoelectric UV inkjet equipment, eliminating printhead clogging and crystallization issues. By modifying polysilazane with NDDA long-chain diacrylate grafts, active acrylic double bonds and compatible segments are introduced into the inorganic silicon-nitrogen backbone, solving the industry pain points of poor compatibility between pure polysilazane and acrylic monomers and polyurethane resins, and coating storage stratification failure. After curing, the coating forms a dual protective structure of silazane ceramic barrier layer and adamantane dense cage network, which has ultra-high electrical insulation, high temperature ceramic flame retardancy, long-term resistance to lithium battery electrolyte immersion, resistance to 85℃ / 85RH damp heat aging, and resistance to cracking under cold and hot cycles. It can meet the stringent safety requirements of precision local insulation coating for new energy power cell battery boxes and aluminum shells. There are no VOC emissions throughout the process, the coating has high utilization rate, and strong industrial adaptability.

[0099] Furthermore, this application provides a method for preparing the above-mentioned solvent-free flame-retardant insulating UV inkjet coating for battery cells, comprising the following steps:

[0100] S1. Resin premixing: Add polysilazane-grafted NDDA oligomer and polyurethane polycarbonate acrylate resin to a room temperature sealed dispersion vessel, and stir at low speed for 5-10 minutes until the system is completely miscible and transparent;

[0101] S2. Low viscosity control: Add adamantane-based diamond cage-like acrylate monomers in batches, stir at medium speed for 10-20 minutes, monitor the viscosity online, and control the viscosity of the finished product system at 25℃ to 10-100 cps.

[0102] S3. Filler dispersion and grinding: Add nano-insulating and flame-retardant composite filler, disperse at high speed for 10-20 minutes, then transfer to a sand mill for circulating grinding until the slurry particle size D50 < 0.5 μm;

[0103] S4. Light-shielding additive compounding: Cool the slurry to below 40℃, add UV compound photoinitiator and UV functional additive in a light-shielding environment, and mix evenly by low-speed light-shielding stirring for 10-20 minutes.

[0104] S5. Precision filtration and packaging: Impurities are filtered using two-stage 0.2μm PTFE precision filter membranes, and the product is stored in a light-proof and sealed environment to obtain a solvent-free UV inkjet insulating coating.

[0105] In this embodiment, the premixing of the core film-forming components is completed. Medium- and high-speed stirring can make the resin and monomer fully miscible to form a uniform main matrix, which provides a basis for the uniform dispersion of subsequent additives. The stirring time of 10-15 minutes can ensure that the system is mixed evenly, while avoiding the introduction of too many air bubbles due to excessive stirring time.

[0106] Optionally, the following steps are also included:

[0107] S1-3. Filler dispersion and grinding: Add nano-insulating and flame-retardant composite filler, disperse at high speed for 10-20 minutes, then transfer to a sand mill for circulating grinding until the slurry particle size D50 < 0.5 μm;

[0108] In this embodiment, a nano-insulating and flame-retardant composite filler is introduced. Medium-speed stirring allows the leveling agent and adhesion promoter to be evenly dispersed in the base material, fully leveraging their effects of improving spreading and enhancing adhesion. Optionally, a colorant can also be added in this step. Blue colorant is preferred to match the industry standard of using blue for the insulation layer of power battery cells, facilitating identification and quality inspection during production and assembly.

[0109] S1-4, Light-shielding additive compounding: Cool the slurry to below 40℃, add UV compound photoinitiator and UV functional additives in a light-shielding environment, and stir at low speed in the dark for 10-20 minutes to mix evenly.

[0110] Optionally, the process also includes the following steps: S1-5, precision filtration and packaging: impurities are filtered using two-stage 0.2μm PTFE precision filter membranes, and the product is stored in a light-proof and sealed environment to obtain the finished solvent-free UV inkjet insulating coating.

[0111] In summary, this invention discloses a method for preparing a solvent-free flame-retardant insulating UV inkjet coating for power battery cells. The steps include: dissolving polysilazane-grafted NDDA oligomer and polyurethane polycarbonate acrylate resin by stirring to obtain a pre-dispersion; adding adamantane-based diamond cage-like acrylate monomer and stirring until homogeneous; adding nano-insulating and flame-retardant composite filler and dispersing at high speed; adding a compounded photoinitiator and UV functional additives after cooling and stirring at low speed in the dark until homogeneous; and finally, bottling after precision filtration. This process is simple and controllable, requires no special equipment, and can be produced using existing UV coating production lines. The resulting coating has stable viscosity and meets the required fineness, and can be directly adapted to mainstream UV inkjet equipment, meeting the mass production needs of insulating coating for power battery cells.

[0112] The above description is merely a specific embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any person skilled in the art can easily conceive of various equivalent modifications or substitutions within the technical scope disclosed in the present invention, and these modifications or substitutions should all be covered within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.

Claims

1. A solvent-free, flame-retardant, insulating UV inkjet coating for battery cells, characterized in that, By weight, including: Polysilazane-grafted NDDA oligomer: 40-50 parts; Adamantane-based diamond cage-like acrylate monomers: 30-40 parts; Polyurethane polycarbonate acrylate resin: 10-20 parts; UV composite photoinitiator: 6-8 parts; Nano-insulating and flame-retardant functional filler: 1-2 parts; UV-specific functional additives: 0.5-2.0 parts.

2. The solvent-free flame-retardant insulating UV inkjet coating for battery cells as described in claim 1, characterized in that, The polysilazane-grafted NDDA oligomer was prepared by hydrosilylation grafting of organopolysilazane with 1,9-nonanediol diacrylate (NDDA).

3. The solvent-free flame-retardant insulating UV inkjet coating for battery cells as described in claim 1, characterized in that, The adamantane-based diamond cage-like acrylate monomers include at least two of the following: 1,3-adamantane diol diacrylate, 1-adamantyl methacrylate, and adamantane monovinyl ether.

4. The solvent-free flame-retardant insulating UV inkjet coating for battery cells as described in claim 1, characterized in that, The polyurethane polycarbonate acrylate resin is a bifunctional flexible polyurethane acrylate synthesized by stepwise addition of aliphatic polycarbonate diol, diisocyanate, and hydroxyethyl acrylate.

5. The solvent-free flame-retardant insulating UV inkjet coating for battery cells as described in claim 1, characterized in that, The UV composite photoinitiator is composed of 2,4,6-trimethylbenzoyl diphenylphosphine oxide (TPO) and 1-hydroxycyclohexylphenyl ketone (184).

6. The solvent-free flame-retardant insulating UV inkjet coating for battery cells as described in claim 1, characterized in that, The nano-insulating and flame-retardant functional filler is a compound system of nano-fumed silica, nano-aluminum nitride, and modified phosphorus-based nano-flame-retardant powder.

7. The solvent-free flame-retardant insulating UV inkjet coating for battery cells as described in claim 1, characterized in that, The UV-specific functional additives include polyether-modified silicone leveling agents, acrylate defoamers, and hindered phenolic UV storage polymerization inhibitors and stabilizers.

8. A method for preparing a solvent-free flame-retardant insulating UV inkjet coating for battery cells, used to prepare the solvent-free flame-retardant insulating UV inkjet coating for battery cells as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Resin premixing: Add polysilazane-grafted NDDA oligomer and polyurethane polycarbonate acrylate resin to a room temperature sealed dispersion vessel, and stir at low speed for 5-10 minutes until the system is completely miscible and transparent. S2. Low viscosity control: Add adamantane-based diamond cage-like acrylate monomers in batches, stir at medium speed for 10-20 minutes, monitor the viscosity online, and control the viscosity of the finished product system at 25℃ to 10-100 cps. S3. Filler dispersion and grinding: Add nano-insulating and flame-retardant composite filler, disperse at high speed for 10-20 minutes, then transfer to a sand mill for circulating grinding until the slurry particle size D50 < 0.5 μm; S4. Light-shielding additive compounding: Cool the slurry to below 40℃, add UV compound photoinitiator and UV functional additive in a light-shielding environment, and mix evenly by low-speed light-shielding stirring for 10-20 minutes. S5. Precision filtration and packaging: Impurities are filtered using two-stage 0.2μm PTFE precision filter membranes, and the product is stored in a light-proof and sealed environment to obtain a solvent-free UV inkjet insulating coating.

9. The method for preparing the solvent-free flame-retardant insulating UV inkjet coating for battery cells according to claim 8, characterized in that, Prior to step S1, the preparation process of the polysilazane-grafted NDDA oligomer includes the following steps: S10: Under the protection of a nitrogen inert atmosphere, the organopolysilazane is heated to 70-80℃; S20: Add NDDA monomer and platinum-based hydrosilylation catalyst dropwise, and maintain the temperature for 5-7 hours; S30: After the reaction is complete, a small amount of small molecule byproducts are removed by vacuum, and the product is cooled and discharged to obtain a transparent modified oligomer.